Optimization studies on development and evaluation of papain-based in situ gelling system for chemomechanical caries removal. (20th May 2014) - Tripathi, Ravi Shankar; Pathak, Kamla
Abstract: Context : Chemomechanical caries removal is a non-invasive technique that eliminates infected dentine via a chemical agent. Papain, owing to its proteolytic nature causes disruption of degraded collagen fibrils that helps easy removal of the caries and has both bacteriostatic and bactericidal action. Objective : The objective of the present work was to formulate and evaluate papain-based in situ gelling system for chemomechanical caries removal, based on the concept of pH-triggered in situ gelation and evaluate its pharmaceutical and chemomechanical characteristics. Material and methodology : A 3 2 full factorial design was employed to formulate the in situ gels. Carbopol 934 and HPMC K15M were designated as two independent variables, each utilized at three different levels and the dependent variables were gelling capacity, viscosity and % cumulative drug permeated (CDP). The optimized formulation was assessed for ex vivo clinical efficacy by SEM, micro-tensile bond strength and antibacterial activity. Results : Formulation F3 with % CDP of 10.13 ± 0.43% and optimum gelling and viscosity characteristics was optimized. The efficacy of F3 was confirmed by enhanced micro-tensile bond strength of 38.48 ± 4.14 Mpa compared to 29.42 ± 2.33 Mpa of control group and SEM. Conclusion : An economically viable papain-based in situ gelling system with clinical potential for caries removal with enhanced bonding ability was successfully developed.